A particle population analysis in Ti- and Al- deoxidized Hadfield steels. (4th May 2018) - Siafakas, Dimitrios; Matsushita, Taishi; Lauenstein, Åsa; Ekerot, Sven; Jarfors, Anders E. W.
Abstract: A quantitative analysis of the amount, size and number of particles that precipitate in situ in titanium- and aluminium-treated Hadfield steel cast during pilot-scale experiments has been performed. SEM with EDS and automated particle analysis abilities was utilized for the analysis. Additionally, Thermo-Calc was used for thermodynamic calculations and Magma 5 for solidification and cooling simulations. Predicted particles sizes calculated with a model based on the Ostwald ripening mechanism were compared with the experimental data. The effect of solute availability, cooling rate and deoxidation practice on the particle population characteristics was determined. It was concluded that the amount, size and number of precipitating particles in Hadfield steel castings is possible to be controlled according to certain requirements by a careful selection of proper additives in proper amounts and also by the optimization of the casting process in aspects of deoxidation timing and control of the cooling rate of the castings.